2018
DOI: 10.1016/j.hpb.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

A predictive nomogram to identify factors influencing the success of a concomitant laparoscopic cholecystectomy with common bile duct exploration for choledocholithiasis

Abstract: LCBDE is useful for the treatment of choledocholithiasis. However, patients who were predicted to have an elevated risk for open conversion might not be ideal candidates for the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
2
11
1
Order By: Relevance
“…Today, although conventional laparoscopic surgery has become the gold standard for straightforward cholecystectomies with reported open conversion rates of <5%,[ 23 24 ] its use for more complicated biliary operations such as bile duct stones, biliary strictures, Mirizzi syndrome, gallbladder malignancy, biliary malignancies and even severe cholecystitis remain more limited and is associated with relatively high open conversion rates of up to 40%. [ 5 25 26 ] Similarly, although MIPS is increasingly adopted worldwide,[ 27 28 ] the most common approach for PS remains the conventional open approach, and many surgeons remain skeptical about MIPS. [ 29 ] The main concerns raised today by opponents of MIPS are its reproducibility and universal applicability due to the long and steep learning curve reportedly required to learn MIPS and to achieve proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Today, although conventional laparoscopic surgery has become the gold standard for straightforward cholecystectomies with reported open conversion rates of <5%,[ 23 24 ] its use for more complicated biliary operations such as bile duct stones, biliary strictures, Mirizzi syndrome, gallbladder malignancy, biliary malignancies and even severe cholecystitis remain more limited and is associated with relatively high open conversion rates of up to 40%. [ 5 25 26 ] Similarly, although MIPS is increasingly adopted worldwide,[ 27 28 ] the most common approach for PS remains the conventional open approach, and many surgeons remain skeptical about MIPS. [ 29 ] The main concerns raised today by opponents of MIPS are its reproducibility and universal applicability due to the long and steep learning curve reportedly required to learn MIPS and to achieve proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…rates of less than 5%, 13,14 its use for more complicated biliary surgeries such as bile duct stones, complicated gallstone disease (gangrenous cholecystitis, Mirizzi syndrome), gallbladder cancer and bile duct cancers remain more limited and is still reported to be associated with relatively high open conversion rates of up to 40%. [14][15][16][17]20 Hence, many surgeons still elect to approach these procedures via the traditional open approach. Presently, with advancements in surgical technique and technology, increasing reports of laparoscopic bilio-enteric anastomosis for various indications such as choledochal cysts and bile duct cancers, [10][11][12]22 have been reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17]20 Hence, many surgeons still elect to approach these procedures via the traditional open approach. [14][15][16][17]20 Hence, many surgeons still elect to approach these procedures via the traditional open approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The open conversion rate of LCBDE varies from 4.2 -43.1%. [20][21][22] Multivariable analysis indicated that the conversion to open surgery was associated with the maximal CBDS diameter (odds ratio, [OR] 2.23), edema of CBD (OR 12.5), and the number of stones (OR 3.438). 21 Another report found that prior antibiotic use (OR 2.98), previous ERCP (OR 4.99), and abnormal biliary anatomy (OR 9.37) were predictors of failed LCBDE.…”
Section: Discussionmentioning
confidence: 99%